2017
DOI: 10.3732/ajb.1600428
|View full text |Cite
|
Sign up to set email alerts
|

Nectar properties and the role of sunbirds as pollinators of the golden‐flowered tea (Camellia petelotii)

Abstract: The nectar sugar composition of species was characterized by sucrose dominance. In addition, the large reduction in seed set when birds are excluded in the golden-flowered tea also supports the suggestion that these winter-flowering plants may have evolved with birds as significant pollinators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…; Fang, Chen, & Huang, , Eriobotrya Lindl. ; Sun, Huang, Chen, & Huang, , Camellia L.), the present study is the first to fully document specialized pollination by honeybees in fall–winter flowering plants, and thereby it explicitly indicates that the bee pollination niche could be available to temperate plant species even during mid‐winter. Japanese C. dayanum plants have the following floral morphological traits that appear to reflect specialized pollination by A. cerana japonica : (a) the dimensions of the labellum chamber, formed by the column and labellum, correspond to the body size of the worker honeybee; (b) the strongly recurved apex of the labellum enables the precise deposition of pollinaria on the honeybee's scutellum; and (c) the oblong viscidium is appropriate for adhering to the scutellar surface.…”
Section: Discussionmentioning
confidence: 61%
“…; Fang, Chen, & Huang, , Eriobotrya Lindl. ; Sun, Huang, Chen, & Huang, , Camellia L.), the present study is the first to fully document specialized pollination by honeybees in fall–winter flowering plants, and thereby it explicitly indicates that the bee pollination niche could be available to temperate plant species even during mid‐winter. Japanese C. dayanum plants have the following floral morphological traits that appear to reflect specialized pollination by A. cerana japonica : (a) the dimensions of the labellum chamber, formed by the column and labellum, correspond to the body size of the worker honeybee; (b) the strongly recurved apex of the labellum enables the precise deposition of pollinaria on the honeybee's scutellum; and (c) the oblong viscidium is appropriate for adhering to the scutellar surface.…”
Section: Discussionmentioning
confidence: 61%
“…; Sun et al . ). We contribute to these previous findings by showing that besides floral traits per se , which in our study correlate with the relative importance of hummingbirds versus insects, differences in PE are also associated with pollinator availability across elevational/environmental gradients.…”
Section: Discussionmentioning
confidence: 97%
“…Rhythms of nectar secretion have been observed to match activity patterns of the most effective pollinators (Herrera, ; Sun et al, ). In F. kwangsiensis , the rate of nectar secretion increased in the early morning (04:00–06:00 h) and gradually decreased thereafter, and the sugar concentration was consistently low (<10%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ex situ conservation of this endangered plant relies on maintenance of the interactions between plants and sunbirds. A recent study on winter‐flowering Camellia species indicated that sunbirds, rather than honeybees, were potentially effective pollinators (Sun et al, ). The low seed production in the tea‐oil tree, Camellia oleifera Abel, an important oil crop plant, could be attributed to a loss of effective pollinators in that most transplantation was to the north of its native area (South China), outside the sunbird foraging range.…”
Section: Discussionmentioning
confidence: 99%